PENINGKATAN LOYALITAS KARYAWAN MELALUI MOTIVASI, LINGKUNGAN KERJA, DAN KOMPENSASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Rusly, M. Asyrofar; Ahmadi, Hanif (Jurnal Ilmiah Sultan Agung, 2025)
This study aims to analyze the influence of motivation, work environment and compensation on loyalty through job satisfaction as an intervening variable at the Tofu Merpati Factory in Probolinggo City. Loyalty is seen as an important factor in determining the Company's comfort. The exogenous variables studied were motivation, work environment, and compensation, while the endogenous variables analyzed were loyalty and job satisfaction as intervening variables. The data was collected through an online questionnaire that was distributed to employees of the Tofu Merpati Factory. This study uses the explanatory research method. The results of the study showed that 1) motivation had a positive and significant effect on job satisfaction, 2) the work environment did not have a positive and significant effect on job satisfaction, 3) compensation had a positive and significant effect on job satisfaction, 4) motivation did not have a positive and significant effect on loyalty 5) the work environment did not have a positive and significant effect on loyalty, 6) compensation did not have a positive and significant effect on loyalty, and 7) job satisfaction does not have a positive and significant effect on loyalty. Keywords: Motivation, Work Environment, Compensation, Job Satisfaction, Loyalty